2016
DOI: 10.1039/c6ra02335e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of additives on microstructure, mechanical and tribological properties of nanocrystalline Zn–Ni coatings in a novel alkaline bath

Abstract: Nanocrystalline Zn–Ni coatings with excellent wear resistance can be obtained from a novel alkaline bath. Meanwhile, the effects of additives and Ni content in deposits on wear behaviors and the wear mechanism of Zn–Ni coatings are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…This is a situation that negatively affects the quality of the coating. Salt complexes such as tetraethylene pentamine are used to prevent the precipitation of Ni ions [35,36]. Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…This is a situation that negatively affects the quality of the coating. Salt complexes such as tetraethylene pentamine are used to prevent the precipitation of Ni ions [35,36]. Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…The oxide film has acted as a lubricant for Zn-Ni coating, and hence its formation is necessary for good frictional characteristics. By adding additives into a novel alkaline plating bath, Feng et al [127] produced a bright Zn-Ni (13.23 wt.%) coating that exhibited lower and more stable friction coefficient of 0.4 than 0.5-0.7 of dull Zn-Ni (15.13 wt.%) coatings deposited without additives. Such an improvement was attributed to the smooth and compact morphology formed when Ni-content decreased with the addition of additives.…”
Section: Frictional Characteristicsmentioning
confidence: 99%
“…According to this proposal, subjecting the CNTs to acidic conditions resulted in opening up the functionalized side, aer which a cyclo addition on the CNT took place, with the imidazole primary nitrogen atom sharing a pair of electrons with the CNT carboxylic cation to form the covalent N-C bond. [47][48][49]…”
Section: Corrosion Inhibition Studiesmentioning
confidence: 99%
“…Then, corrosion inhibition in a salt medium of the zinc–nickel (Zn–Ni) alloy coated with Zn-citrate was investigated by Khan et al 3 Furthermore, friction studies of the 5,50-dimethylhydantoin (DMH)-coated Zn–Ni alloy were carried out by An et al 4 They suggested the occurrence of an increase as well in friction efficiency with an increased concentration of additive. With a chromium–nickel (Cr–Ni) alloy protected by liquid polymer, corrosion of the pure Ni alloy at 700 °C resulting from the addition of sodium sulphate was investigated by YuasacaIchikawa et al 5–7 The results indicated that the effect of sodium sulphate decreased as phase transfer occurred at high temperature. Furthermore, inhibition of Ni–Co alloy corrosion in lithium (Li)-based molten salt was investigated by Lee et al Their results suggested that high concentrations of Cr increased granular corrosion.…”
Section: Introductionmentioning
confidence: 99%